2008
DOI: 10.1183/09031936.00099808
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resection for lung cancer

Abstract: Sublobar resection for small lung cancers has been debated frequently and is still a controversial issue. The only randomised trial comparing lobectomy with sublobar resections found a significantly higher recurrence rate for the latter, but failed to show significant differences in survival, although survival was better for the lobectomy group. One meta-analysis and several nonrandomised comparisons have confirmed these results. In general, lobectomy and sublobar resections have similar 5-yr survival rates. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 60 publications
1
66
0
8
Order By: Relevance
“…Many retrospective studies mainly coming from Japan, showed that for small, early NSCLC sublobar resection may be an oncologically valid procedure, also for low risk patients who might tolerate a major lung resection. In a review of sublobar resection segmentectomy yielded similar results as lobectomy for tumors ≤2 cm (20). In a meta-analysis of sublobectomy versus lobectomy published in 2012 similar results for overall survival were found for stage IA NSCLC ≤2 cm with a hazard ratio of 0.81 (21).…”
Section: Editorialsupporting
confidence: 51%
“…Many retrospective studies mainly coming from Japan, showed that for small, early NSCLC sublobar resection may be an oncologically valid procedure, also for low risk patients who might tolerate a major lung resection. In a review of sublobar resection segmentectomy yielded similar results as lobectomy for tumors ≤2 cm (20). In a meta-analysis of sublobectomy versus lobectomy published in 2012 similar results for overall survival were found for stage IA NSCLC ≤2 cm with a hazard ratio of 0.81 (21).…”
Section: Editorialsupporting
confidence: 51%
“…That study was, however, criticized due to inconsistencies regarding the collection of data; several non-anatomical resections (wedges) were included in the "limited" resection group, which may have altered the overall outcome of the study. More importantly, the aforementioned study unfortunately shed light on the discrepancies and the multitude of variables among data investigated and reported in different studies (7,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…These two types of resections are distinctly different, both in technical and oncological features (7,10). Additionally, the amount of parenchyma removed per case may vary.…”
mentioning
confidence: 99%
See 2 more Smart Citations